Sistem Pendukung Keputusan Pemilihan Laptop untuk Kebutuhan Kuliah Metode Simple Additive Weighting (SAW) - Kurniawan, Rifqi; Majalista, Riya; Ramadhan, Agil; Mirando, Rahmad Dwiki (Indo-MathEdu Intellectuals Journal, 2025)
Laptops are essential devices that support various academic activities for university students, such as writing assignments, programming, graphic design, and attending online classes. However, the wide range of available laptops with varying specifications and prices often makes it difficult for students to choose one that fits their needs and budget. This study aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assist students in selecting the most suitable laptop based on several relevant criteria. This research is a quantitative descriptive study. Data was collected using questionnaires and literature studies. The test results show that the system can accurately and efficiently generate laptop recommendations that align with user preferences. The conclusion of this study indicates that the application of the SAW method in a DSS is effective in simplifying the decision-making process for selecting laptops for academic purposes.